Aortic dissection masquerading as a code stroke: A single-centre cohort study. (March 2020) - Guglielmi, Valeria; Groeneveld, Nina-Suzanne; Posthuma, Laura; Groot, Adrien E; Majoie, Charles BLM; Talacua, Hanna; Kaya, Abdullah; Boekholdt, S Matthijs; Planken, R Nils; Roos, Yvo BWEM; Coutinho, Jonathan M
Abstract: Introduction: Data on the incidence of acute aortic dissection in the code stroke population are scarce. We report estimated incidence, clinical manifestations, treatment and outcomes of patients with an acute aortic dissection in a code stroke cohort from a comprehensive stroke centre. Patients and methods: We used data from a single-centre prospective registry of consecutive adult patients who presented to the emergency department between 2015 and 2018 with neurological deficits suggestive of an acute stroke ('code stroke'). All patients routinely underwent non-contrast computed tomography of the brain and computed tomography-angiography of the aortic arch, cervical and intracranial arteries. Results: Of 2874 code stroke patients, 1563 (54.4%) had acute ischaemia (ischaemic stroke or transient ischaemic attack). Fifteen patients (0.5% of code stroke patients and 0.8% of patients with acute ischaemia) had an acute aortic dissection (all Stanford classification type A). Discerning clinical manifestations were decreased consciousness in 11/15 (73%), pain in 8/15 (53%) and low systolic blood pressure (mean 106 mmHg, SD30). Acute aortic dissection was an incidental finding during computed tomography-angiography in 4/15 (27%). Two out of 15 patients (13%) received intravenous thrombolysis, 9/15 (60%) underwent aortic surgery and 10/15 (67%) died. Of those who survived, 3/5 (60%) had a good functional outcome (modified Rankin Scale 0–2). Discussion and Conclusion: In our comprehensive stroke centre, about 1/200 code stroke patients and 1/125 patients with acute ischaemia had an acute aortic dissection. Multicentre studies are necessary to acquire a more reliable estimate of the incidence of acute aortic dissection in the code stroke population. Given the ramifications of missing this diagnosis, imaging of the entire aortic arch is important in these patients.